IDENTIFIKASI KEMAMPUAN MENGGAMBAR DIAGRAM BENDA BEBAS DAN MEREPRESENTASIKAN GAYA DALAM PENYELESAIAN SOAL TENTANG HUKUM NEWTON - Rikiy Hudamaulana; Sri Astutik; supeno supeno; Binar Kurnia Prahani (FKIP e-PROCEEDING, 2018)
The purpose of this research was to described the student ability in identified free body diagram picture and force representation in finishing question about Newton’s law at Senior High School 1 Arjasa Jember on qualitative scale. The type of this research method was descriptive qualitative. The sample of this research was determined using the method of purposive sampling and it was 37 students at class of XI IPA 3. The data was taken through admission filling of presence list by students and giving written test about Newton’s law which consist of four questions that was inclined plane question, stacked objects question, static objects question, and pulley question by researcher. Assessment was did using assessment’s rubric for quantitative data and scale’s rubric for qualitative data. The result of data analysis was showed that most criteria were achieved for ability of drawing free body diagram in inclined plane question were good, most criteria in stacked objects question were very good, most criteria in static objects question were less, and most criteria in pulley question were good. Meanwhile the result of data analysis was also showed that most criteria were achieved for ability of force representation in inclaned plane question were less, most criteria in stacked objects question were medium, most criteria in static objects question were medium, and most criteria in pulley question were very less. Key word: Ability identification, free body diagram, force representation